Nilai-Nilai Moderasi Beragama dalam Tradisi Keagamaan Masyarakat Muslim Nusantara - Rifqi Halim (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
Religious moderation is a crucial issue in Indonesia's multicultural and pluralistic society. In this context, the religious traditions of the Muslim community in the Indonesian archipelago play a strategic role as a medium for internalizing moderate Islamic values. This study aims to identify the values ​​of religious moderation embodied in the Muslim religious traditions of the Indonesian archipelago, analyze their manifestations, and explain their relevance in maintaining social harmony. This study employed a qualitative approach using library research. Data were obtained from various literature sources, including books, journal articles, and official documents discussing Islam Nusantara, religious moderation, and Islamic religious traditions. The data were analyzed descriptively and analytically through data reduction, categorization, and interpretation. The results indicate that the Muslim religious traditions of the Indonesian archipelago embody values ​​of religious moderation such as tolerance, balance, inclusivity, and respect for diversity. These traditions serve as a means of strengthening social cohesion and harmonizing religious life. Thus, the religious traditions of the Indonesian archipelago hold significant relevance in strengthening religious moderation amidst social dynamics and global challenges.